Airline service: low-cost-carriers (LCCs) failure and passenger emotional experience. Issue 3 (18th September 2021) - Herjanto, Halimin; Amin, Muslim; Okumus, Fevzi; Cobanoglu, Cihan
Abstract : Purpose: This study aims to analyze low-cost-carrier (LCC) passengers' comments about their flight experience on Asian LCCs. Design/methodology/approach: A netnography approach was used to review and content analyzed 230 LCC passengers' negative feedback on the TripAdvisor website. Findings: LCC service failures generated 17 different negative emotions; among them, shock, disappointment and surprise were the most frequent emotions felt by passengers. Practical implications: Maintaining a high level of customer service and ensuring easy access to information reduces LCC passenger's negative emotions and meets LCC passengers' service expectations and satisfaction. This study provides guidelines for the LCCs management who want to implement a netnography technique as a marketing research strategy. Originality/value: A better understanding of this concept will help the LCCs industry to build a robust business model than competitors, maintain their competitive advantages in the global market and develop effective marketing strategies to attract more passengers. Abstract : 航空服务：低价航空公司 (lcc) 服务失误和乘客情感体验摘要: 研究目的 –: 本文旨在分析低价航空公司乘客对他们在亚洲低价航空飞行体验的评价。 设计/研究方法/路径 –: 本研究使用网络志方法审查和内容分析了230名低价航空乘客在TripAdvisor网站上的负面评价。 研究结果 –: 低价航空公司的服务失误共产生了17种不同的负面情况。其中, 震惊、失望、惊讶为乘客最常感受到的情绪。 实践意义 –: 保持高水平的客户服务并确保其轻松获取有效信息可以减少低价航空公司乘客的负面情绪, 提高他们的服务期望和满意度。本研究为拟实施网络志技术作为营销研究策略的低价航空公司管理人员提供了指导意见。 原创性/价值 –: 更好地理解这一概念将有助于低价航空行业建立起比竞争对手更稳健的商业模式, 保持其在全球市场的竞争优势, 并制定有效的营销策略以吸引更多乘客。 Abstract : Sevicio de aerolineas: problemas con provedores de bajo costo y experiencias emocionales de pasajerosResumen Propósito: Este estudio analizó los comentarios sobre la experiencia de vuelo de los pasajeros de las aerolíneas de bajo costo (LCCs, por sus siglas en inglés) de Asia. Diseño/metodología/método: Se utilizó un enfoque de netnografía para revisar y analizar el contenido de los comentarios negativos de 230 pasajeros de LCCs en el sitio web de TripAdvisor. Resultados: Las fallas en el servicio de las LCCs generaron 17 emociones negativas diferentes; entre ellas, conmoción, decepción y sorpresa fueron las emociones más frecuentes que sintieron los pasajeros. Implicaciones prácticas: Mantener un alto nivel de servicio al cliente y garantizar un acceso fácil a la información reduce las emociones negativas de los pasajeros de las LCCs y cumple con sus expectativas de servicio y satisfacción. Este estudio proporciona pautas para los gerentes de las LCCs que desean implementar una técnica de netnografía como estrategia de investigación de mercados. Originalidad/valor: Entender mejor este concepto ayudará a la industria de las LCCs a construir un modelo comercial más sólido que el de sus competidores, mantener sus ventajas competitivas en el mercado global y desarrollar estrategias de mercadotecnia efectivas para atraer a más pasajeros. Aerolíneas de bajo costo (LCC), emociones negativas, falla en el servicio, destino turístico